Influence on the oil‐gas accumulation potential of the laminated algal micritic dolomite in Jixian system from Mesozoic magmatic activities at the south‐western margin of the Ordos Basin, China. (20th September 2017) - Liu, Futian; Li, Rongxi; Zhao, Bangsheng; Cheng, Jinghua; Li, Delu; Wu, Xiaoli; Li, Sanzhong
Abstract : The Mesoproterozoic Jixian System is widely distributed at the south‐western margin of the Ordos Basin. It is mainly dominated by siliceous laminated algal micritic dolomite that is a set of potential carbonate source rocks. The magmatic activities at the south‐western margin of the Ordos Basin were frequent and intensive, and the Tongcheng intrusion exposed in this area has an intrusive contact relationship with the Jixian System. This paper uses geochemical methods to study the influence of magmatism to lithology, physical properties, hydrocarbon generating property, and geochemistry of the Jixian System. Analysis data reveal that, with the increasing distance to the intrusion, the porosity, permeability, and content of dolomite, trace elements, and rare earth elements in surrounding rock decrease while the density and silica content increase gradually. In addition, the parameters have a weakening trend about adsorbed hydrocarbon ( S 1 ), pyrolysis hydrocarbon ( S 2 ), hydrocarbon generating potential ( S 1 + S 2 ), and pyrolysis peak temperature ( T max ). The results suggest that the magmatic hydrothermalism and the thermal effect of magmatic intrusion changed the physical and geochemical characteristics of the surrounding rock and promoted the hydrocarbon generation of organic matter. However, these characteristics reflect that the magmatic activities only have a relatively small effect on the laminated algal micritic dolomite in Jixian System without a destructive effect at the south‐western margin of the Ordos Basin. The petroleum potential of the Jixian System is worthy to be further explored.